Pharyngeal pressure value using two continuous positive airway pressure devices. Issue 4 (11th March 2008) - Colnaghi, M; Matassa, P G; Fumagalli, M; Messina, D; Mosca, F
Abstract : The aim of the study was to measure the difference between the set continuous positive airway pressure (CPAP) value and the pharyngeal pressure reading during CPAP in premature infants with mild respiratory distress syndrome, using two different devices: hood CPAP and the conventional nasal system. The preliminary results suggest that hood CPAP may produce more stable pharyngeal pressure than the conventional nasal device.